The tyrant-in-the-mind: influences on worker behaviour in a post-totalitarian organization - Eloquin, Xavier (Tyran w umyśle: wpływ na zachowanie pracownicze w organizacji posttotalitarnej, 2016)
This paper is an extended single case study exploring worker behaviour in a post-totalitarian organisation – a large secondary school. It uses theoretical contributions from political science exploring totalitarian regimes and from systems-psychodynamics; specifically ideas of narcissism and the concept of the-organisation-in-the-mind; as well as the concepts of role; task and boundary. It proposes that due to narcissistic needs; a tyrannical leader over-identified with his/her organisation to the extent that his/her own ego needs were merged with organisational needs. This was then taken in by the followers as their version of the organisation-in-the-mind; but with a specific addition: because the tyrant and the organisation are synonymous; they took in an organisational manifestation of the tyrant – the tyrant in the mind. This became the unconscious predicate shaping subsequent organisational behaviour; leading to increased conflict and ineffectiveness. Implications for leaders entering a post-totalitarian organisation and the nature of interventions are discussed; as are further lines of enquiry
Management Forum, 2016, vol. 4, no. 3, s. 41-51
Keywords: organisational totalitarianism; organisational ideal; narcissism; the organisation-in-the-mind; systems psychodynamics; totalitaryzm organizacyjny; ideał organizacyjny; narcyzm; organizacja w umyśle; systemy psychodynamiczne